Measurement of Product Temperature by Use of an Infrared Thermometer - Mahnke, C. W. (1973)
An infrared sensor system to measure product surface temperature in industrial food processes is described. The method is suitable for use in either manufacturing plant or laboratory equipment. Good correlation can be expected between experimental and plant temperature readings.